Vocal Fold Polyps: Literature Review - Vasconcelos,Daniela de (2019)
Abstract Introduction Vocal fold polyps are one of themost frequent benign laryngeal lesions, impacting the quality of life of those affected by them, primarily the vocal production. Despite being a well-established therapy in conjunction with surgery, speech therapy alone may also be effective in treating these lesions. As such, otolaryngologists and speech therapists need updated bibliographic knowledge on the issue. Objective To describe the literature findings on vocal fold polyps that discuss prevalence, etiology, histology, physiopathology, vocal characteristics or treatment. Data Synthesis The present study is a review article based on a bibliographic search using platforms, databases and search engines, with no restrictions on means of publication, methodological quality or language. All the articles on vocal fold polyps pertaining to the object of study published in the past 15 years were included. Among the characteristics investigated, the most discussed were prevalence of men, smoking as an etiological cofactor, the possibility of histological differentiation from vocal nodules, the relationship with cover minor structural alterations, and the indication and effectiveness of different treatment options. Conclusion Despite the discrepancies found in the present literature review on vocal fold polyps, there has been a notable scientific progress in the otolaryngologic techniques and in the effectiveness of speech therapy as initial treatment, with direct and indirect techniques, corroborating the need for scientific investigation of the issue.